2011
DOI: 10.1245/s10434-011-1870-5
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Preoperative Localization Techniques for Patients with Primary Hyperparathyroidism

Abstract: Ultrasound and sestamibi-SPECT are similar in ability to preoperatively localize abnormal parathyroid glands in pHPT. Accuracy may be improved with 4D-CT; however, further investigation is required. Choice of preoperative imaging strategy depends on numerous patient, institutional, and economic factors of which the surgeon must be aware.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
238
1
37

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(290 citation statements)
references
References 25 publications
14
238
1
37
Order By: Relevance
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This could be because patients who underwent DTDP imaging were patients who initially underwent DT imaging and findings from the initial Tc-99m sestamibi and Tc-99m pertechnetate images were deemed insufficient for diagnosis by the nuclear medicine physician on duty thus prompting further delayed imaging, so patients in the DTDP group represented 'difficult' patients which findings were likely to be inconclusive to begin with. Both add-on SPECT and SPECT/CT improved the diagnostic accuracy over planar imaging alone which concurs with previous studies [5,[16][17][18][19]28]. However, SPECT imaging appeared to have a higher diagnostic accuracy than SPECT/CT which is unexpected and contradicts a previous study which demonstrated the superiority of SPECT/CT over SPECT alone [29].…”
Section: Discussionsupporting
confidence: 79%
“…Preoperative localization of hyperfunctioning parathyroid glands can be done by various imaging modalities including ultrasound [5][6][7][8], magnetic resonance imaging [5,9,10], and computed tomography [5]. However, the modality most utilized is nuclear medicine isotopic imaging using various radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…8 4D-CT has been proposed as an alternative or adjunctive method for preoperative localization of abnormal parathyroid glands in patients with primary hyperparathyroidism. [9][10][11][12][13] Multiple recent studies have indicated that 4D-CT may be especially useful for preoperative localization in patients with negative or inconclusive results on sonography and technetium Tc99m sestamibi studies, reoperative parathyroid patients, patients with mild hypercalcemia, and in patients with multigland disease. [14][15][16][17][18] However, previously published reports have predominantly evaluated cohorts with small numbers of patients and have focused on specific patient populations with strict exclusion criteria.…”
mentioning
confidence: 99%
“…When comparing the accuracy in detecting abnormal parathyroid glands between MIBI and USG, some have found that MIBI is more accurate than USG while other studies have found the opposite or similar accuracies. (Cheung et al, 2011) In our experience, MIBI has a higher overall sensitivity, accuracy and positive predicted value (PPV) in detecting abnormal parathyroid glands than USG (85%, 97% vs 94% vs. 57% vs 89%, 56%, respectively). (Lo et al, 2007) In fact, at our institution, we would rely more on the findings of the MIBI than USG.…”
Section: Preoperative Parathyroid Localizationmentioning
confidence: 83%
“…Therefore, the authors concluded that MIBI-SPECT and USG had similar localization ability but 4D-CT may have improved accuracy. (Cheung et al, 2011) …”
Section: Preoperative Parathyroid Localizationmentioning
confidence: 99%